2017
DOI: 10.1016/s0140-6736(17)31744-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of non-steroidal anti-inflammatory drugs for the treatment of pain in knee and hip osteoarthritis: a network meta-analysis

Abstract: Swiss National Science Foundation (grant number 405340-104762) and Arco Foundation, Switzerland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
329
0
35

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 472 publications
(415 citation statements)
references
References 33 publications
9
329
0
35
Order By: Relevance
“…На протяжении длительного периода времени препаратом выбора при лечении пациентов с дорсопатиями и другими болевыми суставно-мышечными синдромами, обусловленными, в частности, остеоартрозом, считался ацетаминофен. Вместе с тем результаты недавно опубликованного мета-анализа продемонстрировали его относительно невысо-кую противоболевую эффективность, незначительно отличающуюся от плацебо, у пациентов с остеоартрозом коленных или тазобедренных суставов при том, что мощ-ное противоболевое действие показал диклофенак [5].…”
unclassified
“…На протяжении длительного периода времени препаратом выбора при лечении пациентов с дорсопатиями и другими болевыми суставно-мышечными синдромами, обусловленными, в частности, остеоартрозом, считался ацетаминофен. Вместе с тем результаты недавно опубликованного мета-анализа продемонстрировали его относительно невысо-кую противоболевую эффективность, незначительно отличающуюся от плацебо, у пациентов с остеоартрозом коленных или тазобедренных суставов при том, что мощ-ное противоболевое действие показал диклофенак [5].…”
unclassified
“…We observed less gastrointestinal adverse events for aceclofenac than in control interventions [RR 0.69 (95% CI: 0.57, 0.83); I assess the heterogeneity (12). Da costa et al (13), based on a recent network meta-analysis of placebo-controlled trials, suggested that diclofenac (150 mg/day) is the most effective NSAID improving both pain and function. On the other hand, van Walsem et al (14), in a network meta-analysis observed that diclofenac (150 mg/day) is likely to be more effective in alleviating pain than celecoxib (200 mg/day), naproxen (1000 mg/day), or ibuprofen (2400 mg/day), and similar to etoricoxib (60 mg/day) (14).…”
mentioning
confidence: 76%
“…This may be because of its widespread use as a reference drug in osteoarthritis trials (19). Recent evidence suggest diclofenac (150 mg/day) as one of the most effective NSAIDs in alleviating pain (13,14). The literature also suggests that acetaminophen is the least effective analgesic, irrespective of the dose (13, 14, 49).…”
Section: Discussionmentioning
confidence: 99%
“…The patients either complete the course as directed or they continue buying and self-treat with the medication, managing the doses on their own and subsequently increasing the dose with increasing pain. This behaviour, which is encouraged by some physicians, can be fatal and has been proven to be useless in most cases of long-term chronic pain management [46].…”
Section: Acetaminophenmentioning
confidence: 99%